2018
DOI: 10.1249/mss.0000000000001432
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Taurine Ingestion on Human Maximal Voluntary Muscle Contraction

Abstract: Taurine ingestion is detrimental to maximal voluntary muscle power and both maximal isokinetic and isometric peak torque in noncaffeine consumers, whereas taurine ingestion in caffeine-deprived caffeine consumers improves maximal voluntary muscle power but has no effect on other aspects of contractile performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Lim et al [36] showed that in people who do not normally consume caffeine, taurine ingestion is detrimental to maximal voluntary muscle power and both maximal isometric and isokinetic peak torque, whereas taurine ingestion in caffeine-deprived caffeine consumers improves maximal voluntary muscle power but has no effect on other aspects of contractile performance.…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al [36] showed that in people who do not normally consume caffeine, taurine ingestion is detrimental to maximal voluntary muscle power and both maximal isometric and isokinetic peak torque, whereas taurine ingestion in caffeine-deprived caffeine consumers improves maximal voluntary muscle power but has no effect on other aspects of contractile performance.…”
Section: Discussionmentioning
confidence: 99%
“…As reported with the above-mentioned acute dietary supplements, taurine supplementation could theoretically alter components of the power-time relationship. For example, aerobically biased (endurance) exercise has typically been improved following taurine supplementation (see Waldron et al 2018a;Souza et al 2017 for reviews) and effects on skeletal muscle function have been reported (Dutka et al 2014;Lim et al 2018), which might collectively explain the improved exercise efficiency following oral administration (Paulucio et al 2017). These mechanistic actions relate to the factors ascribed to govern the balance of CP and W′, which include a loss of muscle efficiency, characterised by distinct metabolic (Jones et al 2008;Vanhatalo et al 2016) and neuromuscular (Burnley et al 2012) profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 19 studies included in this review, sex and athlete type were inextricable variables. Seven of the 19 studies examined athletes [ 2 , 3 , 14 , 41 , 63 , 78 , 81 ]. One study examined soldiers [ 35 ].…”
Section: Results – Overviewmentioning
confidence: 99%
“…Eleven of the studies examined aerobic parameters [ 2 , 3 , 14 , 23 , 35 , 40 , 45 , 51 , 63 , 81 , 91 ]. Eight of the studies examined anaerobic measures or recovery [ 12 , 41 , 44 , 55 , 56 , 78 , 79 , 83 ]. Two of the 19 studies examined VO 2 max outcomes in male athletes [ 81 , 91 ] and two of 19 studies examined women [ 23 , 78 ].…”
Section: Results – Overviewmentioning
confidence: 99%